A Study of Social Media Factors that Affect Online Purchase Intention of Tourist Products and Services in Bangkok, Thailand - Meeporn Oeawpanich, มีพร เอี๋ยวพานิช (Dusit Thani College Journal, 2018)
This researcher has the main objectives to study and find out the social media factors that affect the online purchase intention of tourist product and service. The social media factors which are selected such as the use of social media, social identity, altruism, telepresence, e-word-of-mouth, advertising, ease of use, usefulness and trust are selected. Moreover; the researcher also study the relationship between each social media factor with online purchase intention of tourist product and service in Bangkok, Thailand. This study is based on non-probability convenience sampling where the data was collected and gathered from 400 respondents in five keys selected tourist destinations in Bangkok. To gather the data, the research prepared the self-administrated five-point Likert Scale questionnaire. To analyze the data in details, the researcher used both descriptive and inferential analyses. The result shows that all of the independent variables have positive relationship with dependent variables. The independent variables of the use of social media, social identity, altruism, telepresence, e-word-of-mouth, advertising, ease of use, and usefulness have moderate significant level in the relationship with online purchase intention; moreover, it shows that trust is the only factor which has the strong significant level in the relationship with online purchase intention of tourism product and service in Bangkok, Thailand. . The summaries of hypothesis testing is that all the independent variables have positive relationship with the dependent variable. The independent variables of the Use of Social Media, Social Identity, Altruism, Telepresence, E-word-of-mouth, Advertising, Ease of use, and Usefulness have moderate significant levels in the relationship with online purchase intention; moreover, the Trust has a strong significant level in the relationship with online purchase intention of tourism product and service. The findings of this study will help the tourist product and service providers and entrepreneur to better understand the change in consumer behavior that is the use of social media as the main tool for searching travel information and making the online booking and purchase.